Self-sustainable energy efficient long range WiFi network for rural communities - Khairuddin, Ab Hamid; Chong, Eng Tan; Sei, Ping Lau (IEEE, 2012)
WiFi is a cost effective technology of choice for network extension in the rural areas. The telecentre network can reach further to the nearby villages within 10km radius by the use of long range WiFi relay points. The challenges encountered will be the self-sustainability of the network. It should be highly energy efficient and to be powered by the very limited energy sources available in the rural environment. In this case, a modular solar based power supply system has been investigated and enhanced to achieve longer operating hours for equipment installed in the middle of the tropical rainforest and on top of a mountain. The overall design of the self-sustainable long range WiFi network model and the end-user wireless terminal shall also meet the conditions of the rural as well as the living pattern of the local people. The proposed network model has been successfully deployed in a remote village in Borneo, named Bario, connecting six nearby villages to the telecentre for Internet access.